Professional-scientific competence orientation in the context of polyvalent qualification developments : developments, problems and perspectives in Germany, USA and beyond - Rein, Volker [Verfasser] (My University, 2022)
"The increasingly science-based requirements in all areas of society worldwide necessitate a corresponding conceptual orientation of qualifications in professionlisation. So far, this has not led to compatible design of educational programmes within academic education and across sectors due to differently oriented competence references to scientific and professional requirements. Using the example of academic education in Germany and the USA, this contribution discusses conceptual-analytical and empirical research findings on the prerequisits and characteristics of professional-scientific competence acquisition for the corresponding design of curricula in Associate's programmes (USA only), Bachelor's and Master's degree programmes in selected disciplines at academic institutions in both countries. The research interest focused in particular on relevant approaches to competence-related concepts, instruments and practices that enable a compatible relationship between academic subject systematics and professional action systematics. The contribution futher discusses the findings generated on characteristics that could be regarded as constitutive for professional-scientific competence acquisition and for the corresponding design of study programmes, despite differences in qualifications and subjects as well as in the educational system. A holistic and educationally embedded understanding of professional-scientific competence as well as competences or areas of competence that apply towards subjects were identified as suitable for this. This could be effective level related and polyvalent in an operationalisation of learning outcomes related to the respective disciplinary subject and professional requirement areas. Finally, the contribution points out existing problems and further research questions as well as possible development options for the design features of professional-scientific competence acquisition." (Author's abstract, BIBB-Doku)
Keywords: S 1 Stufen der Berufsbildung; S 1.4 Hochschulbildung; G 1.3.1 Bildungsangebot & -nachfrage; S 2.2.4 Anrechnung, Prüfung & Zertifizierung; I 2.1 Deutschland; I 2.3.2 Nordamerika; 370; Berufsbildung; Hochschulbildung; Bildungsabschluss; Anrechnung von Bildungsleistungen; Qualifikationsrahmen; Internationaler Vergleich; Bundesrepublik Deutschland; USA